2011
DOI: 10.1103/physrevlett.107.016803
|View full text |Cite
|
Sign up to set email alerts
|

Spin-Polarized to Valley-Polarized Transition in Graphene Bilayers atν=0in High Magnetic Fields

Abstract: We investigate the transverse electric field (E) dependence of the ν=0 quantum Hall state (QHS) in dual-gated graphene bilayers in high magnetic fields. The longitudinal resistivity (ρxx) measured at ν=0 shows an insulating behavior which is strongest in the vicinity of E=0, and at large E-fields. At a fixed perpendicular magnetic field (B), the ν=0 QHS undergoes a transition as a function of E, marked by a minimum, temperature-independent ρxx. This observation is explained by a transition from a spin polarize… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
69
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 23 publications
8
69
1
Order By: Relevance
“…The graphene analog of the chemical potential µ term which tunes transitions between antiferromagnetic and d-wave superconducting states in the HTS case, is a sublatticestaggered potential v . Interestingly this field is easily tunable experimentally [34][35][36][37] in the bilayer graphene case. SO(5) symmetry in HTS is conjectured to emerge in low-energy effective theory 21 , and can be exactly realized in extended Hubbard model with artificial longrange interactions 38,39 ; however, it never becomes exact for commonly used models like t − J or Hubbard model.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The graphene analog of the chemical potential µ term which tunes transitions between antiferromagnetic and d-wave superconducting states in the HTS case, is a sublatticestaggered potential v . Interestingly this field is easily tunable experimentally [34][35][36][37] in the bilayer graphene case. SO(5) symmetry in HTS is conjectured to emerge in low-energy effective theory 21 , and can be exactly realized in extended Hubbard model with artificial longrange interactions 38,39 ; however, it never becomes exact for commonly used models like t − J or Hubbard model.…”
Section: Discussion and Summarymentioning
confidence: 99%
“…In particular, a quantum spin Hall analogue has been predicted at ν = 0 in bilayer graphene if the ground state is a spin ferromagnet 8,9 . Previous studies have demonstrated that the bilayer ν = 0 state is an insulator in a perpendicular magnetic field [10][11][12][13][14][15][16] , though the exact nature of this state has not been identified. Here we present measurements of the ν = 0 state in a dual-gated bilayer graphene device in tilted magnetic field.…”
mentioning
confidence: 99%
“…Transport studies in a dual-gated geometry [12][13][14] indicate that this gapped state results from an interaction-driven spontaneous symmetry breaking in the valley-spin space 17 . However, the exact order of the resulting ground state remains controversial.…”
mentioning
confidence: 99%
See 2 more Smart Citations